Increasing Students' Self-Efficacy Through A Realistic Mathematical Education - Rama Nida Siregar; Sufyani Prabawanto ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2021)
This research is motivated by problems, the low level of students' self-efficacy abilities. One alternative learning that can be applied to improve students' self-efficacy abilities is a realistic mathematical education. The purpose of this study was to determine the increase in students self-efficacy abilities with a realistic mathematical education in mathematics learning, and to determine students' responses to mathematics learning by using a realistic mathematics education. The design used in this study was a pretest-posttest control group research design, with a quasi-experimental method. The population in this study were all class VII students of Al-Ulum Private Junior High School Medan, while the sample in this study were students of class VII 3 as the experimental class and class VII 5 as the control class who were randomly selected class. The instrument used is a self-efficacy questionnaire to see the ability of self-efficacy that has been tested and a questionnaire to see student responses. In this study, data was obtained to see the increase in students 'self-efficacy abilities with a realistic mathematics education in mathematics learning and to see students' responses to mathematics learning using a mathematical education which was analyzed using a Likert attitude scale. Based on the analysis of the results of the self-efficacy questionnaire obtained from the improvement of students' self-efficacy abilities with a realistic mathematics education.